Analisis Kepuasan Pengguna Aplikasi Mobile Banking BCA (M-BCA) dengan Menggunakan Metode Pieces Framework: (Studi Kasus: Pengguna di Wilayah Jakarta Selatan) - Syawli Alivian Irawan; Qori Halimatul Hidayah (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Advances in information technology have driven the transformation of banking services towards digitalization through mobile banking. Bank Central Asia (BCA), one of the largest private banks in Indonesia, offers m-BCA services to facilitate quick, practical, and efficient customer transactions. However, issues such as delayed notifications, system disruptions, and login problems still exist. This study aims to evaluate m-BCA user satisfaction using the PIECES Framework, which consists of six dimensions: Performance, Information, Economy, Control and Security, Efficiency, and Service. A descriptive quantitative approach was used, with a questionnaire distributed to 105 active m-BCA users in South Jakarta. Data were analyzed using mean values to assess satisfaction levels for each dimension, and validity and reliability tests were conducted. The results showed average scores of 4.02 for Performance, 4.08 for Information, 4.08 for Economy, 4.18 for Control and Security, 4.20 for Efficiency, and 4.09 for Service. The overall score of 4.10 falls into the "Satisfied" category. The highest score was for Efficiency, indicating strong support for users’ banking activities, while the Performance dimension scored lower, suggesting room for improvement. Overall, users are satisfied with m-BCA, but system performance improvements are needed for service stability and sustained satisfaction.